Analisis Preferensi Konsumen Dalam Pengambilan Keputusan Keputusan Pada Penggunaan Go-Jek Sebagai Alat Transportasi (Studi Kasus Mahasiswa Brawijaya Malang) - IVAN MUN`IM VARADIAN (Jurnal Ilmiah Mahasiswa FEB, 2017)
Transportation became one of the important supporting factor in daily activities especially in urban areas. The regularity of the city can be created if it has good transport, this happens because transportation is a tool in driving development in the urban areas. In addition, transportation also is an infrastructure for human movement or goods incurred due to activity in urban areas. Indonesian. Malang became one of the more experienced  congestion  on  some  roads.  At  the  time  of  an  increasingly  modern  consumers  like  to  have transportation services that are more practical and innovative. Recently transformed into a taxi-taxi with the birth of professional Go-Jek. Many have welcomed the presence of motorcycle taxis online as an option the model different transport services, but with the taxi pengkolan who did not receive an online presence where they presume that they took a taxi to their consumers online. The dispute between the two sides can not be bending to refer to an online attack action in doing the taxi pangkolan. The purpose of this research is to find out  what  factors  that  shape  consumer  preference  in  the  use  of  Go-Jek  as  means  of  transportation  at  the University of Brawijaya Malang, because at the University a lot of demand for services Go-Jek. The results of  this  research  are  cost,  reliability  and  security  of  a  significant  effect,  while  ease  of  influential  not significantly to consumer preference. Keywords: Consumer Preference, Go-Jek, Analysis Of Factors.